In the Cemetery of the Murdered Daughters: Ingeborg Bachmann's Malina - Sara Lennox (Studies in 20th & 21st Century Literature, 1980)
Bachmann's novel Malina is about the absence of a female voice. The unnamed female I of this novel defines herself with respect to two male figures. Malina is her Doppelgänger, the voice of male reason which women must assume if they wish to speak at all. In relationship to Ivan, her lover, the I constitutes herself as traditionally feminine and suffers the agonies of romantic love. Though evidently miserable, the I must represent herself as content with her position between these two men, simply inversions of one another. Yet the novel also contains another story of the I which cannot be given coherent narrative form, for there is no way to speak who she really is. In the middle section of the novel, entitled «The Third Man,» the I gives expression to her distress and pain in a series of nightmares, in which her father, termed by Bachmann «the murderer whom we all have,» figures as her tormentor. That which patriarchy does not allow to speak here cries out nonetheless. Moreover, counterposed to and subversive of the patriarchal subsumption of women is an archaic and Utopian fantasy of sensual joy and freedom which threads its way through the novel. Though the I disappears at the end of the novel, female desire can't be completely silenced. Contemporary feminists thus can use Bachmann by turning this promise of future happiness against the present misery of women which Malina depicts.
Keywords: Bachmann; Malina; absence; female voice; Doppelgänger; male reason; identity; The Third Man; nightmares; tormentor; patriarchy; Utopian fantasy; female desire